Energy Estimation on BLDC Electric Vehicle using MATLAB - Hasnira Hasnira; Didi Istardi (IPTEK Journal of Proceedings Series, 2014)
The need for an efficient electric drive system which has high torque and speed, low maintenance costs is getting increased. However, the motors which are commonly used, such as induction motors and DC motors, have not been able to meet the need. Therefore, a new model with efficiency System and energy consumption using simulated software "MATLAB ® or Simulink®" is made. This model includes battery, power electronics converters, electric motors, and transmission systems. In this case the energy system during regenerative braking breaking is also taken into account. The result of the efficiency value of the batteries, inverter, electric motor and the total efficiency value of the overall system is gathered from the control Brushless Motor (BLDC) models HHDB 350-1000 Watt and some batteries type  SOC with capacity 34-48 Ah used.